Aperture slot size effect to wide band open air gap radial-line slot array performance - Imran , Mohd Ibrahim; Tharek, Abdul Rahman; Solomon, Zakwoi; Mursyidul Izham, Sabran (WILEY, 2014)
A wideband open air gap radial line slot array (RLSA) antenna is presented for point-to-point application. This article investigates the optimum slot arrangement and the effect of slot width to the RLSA antenna. Eight models were developed and simulated with slot width taking range in values from 1 to 8 mm. Results from simulation shows optimum performance at 6-mm slot width. The 2-mm slot width gave similar performance to the 6-mm slot width in term of gain and directivity. Both antennas were fabricated and measured, from the measurement;a better return loss performance of about 28% was realized at 6-mm slot width when compared to 2-mm slot width RLSA. However, both antennas produced the same gain. A better sidelobe level of 2.9 dB was achieved with the 2-mm slot width antenna.